UNLOCKING THE POTENTIAL OF BLENDED FINANCE MODELS FOR SME GROWTH IN SUB SAHARAN AFRICA - Kamaldeen Ibraheem Nageri (J-MACC, 2026)
Persistent underperformance of SMEs in Sub-Saharan Africa poses a major threat to inclusive economic growth. This study examined the influence of blended finance strategies on SME growth performance, focusing on public-private investment ratio, share of concessional capital, and volume of technical assistance deployed. Using a quantitative research design and secondary data from reputable international development finance databases, the study analyzed 180 SMEs supported through blended finance frameworks between 2015 and 2024. Descriptive statistics, correlation analysis, diagnostic tests, and Ordinary Least Squares regression were conducted to evaluate the relationship between the variables. Findings revealed that all three blended finance strategies had statistically significant and positive effects on SME growth outcomes, including revenue generation, employment creation, and firm survival. Notably, technical assistance emerged as the most influential factor, followed by public-private investment ratio and concessional capital. These results confirm theoretical assumptions from the Resource-Based View and Blended Finance Theory, emphasizing the strategic role of structured financial support in enhancing SME resilience and productivity. Based on these findings, the study recommends the institutionalization of technical assistance, balanced co-financing frameworks, and targeted use of concessional capital to scale SME impact. The insights offer practical value for policymakers, donors, and investors committed to inclusive economic transformation. .